Influence of 'Candidatus Phytoplasma prunorum' on primary and secondary metabolites of apricots - Gabriela Trempetić; Eliška Zezulová; Tomáš Nečas; Petr Šnurkovič; Tomáš Kiss (Plant Protection Science)
'Candidatus Phytoplasma prunorum' ('Ca. P. prunorum') is a causative agent of European stone fruit yellows (ESFY), an economically important decline disease of some stone fruit species (Prunus spp.). The present research focused on the influence of 'Ca. P. prunorum' on primary and secondary metabolites in four apricot genotypes consisting of older trees (genotypes Nora, LEM 159, group 1) and younger trees (genotypes H 74 and H 177, group 2). The content of sugars (glucose, sucrose, fructose and sorbitol), total phenolic content (TPC), total flavonoid content (TFC), antioxidant capacity (AC), total soluble proteins (TSPC), mineral ions: potassium (K+), sodium (Na+), magnesium (Mg2+) and calcium (Ca2+), pigments: chlorophyll a, b and carotenoids, and indolic compounds content (ICC) were analysed in two time periods during the year in the leaves of tested trees. The results revealed that the presence of phytoplasma/ESFY symptoms significantly decreased the content of pigments in both groups during the summer sampling period. ESFY caused a decrease of TPC, TFC and ICC in the H 177 genotype. The phytoplasma decreased the TSPC and K+ content in older trees during both sampling periods. The only increase caused by phytoplasma infection was observed in glucose content, but only in the group of older plants. The results of this study support the idea that 'Ca. P. prunorum' affects metabolites in plants' defence system and manipulates basic metabolic processes during successful infection.